DOI: 10.14418/wes01.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Teachers' Perspectives on Early Mathematics Education

Abstract: First and foremost, I wish to express my deepest gratitude for the continual guidance, inspiration, and trust from Professor Anna Shusterman, without whom this project and my passion for education would not exist. My life direction has changed ever since she brought me to preschools in my sophomore year. Many thanks to the preschool teachers who participated in this project. I am grateful for their honesty, courage, and willingness to share. Without their insight, this project would not have been possible. Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 32 publications
1
13
0
3
Order By: Relevance
“…The literature review reveals that an excellent pedagogical knowledge has a significant correlation with effective teaching and learning in the classroom (Zamri & Fadhil, 2014;Jamil, 2012;Lo, 2014;Sulatan, Masnan, Rohaizad & Salleh, 2016). Teachers need the knowledge to develop the skills and to design quality learning activities that provide children adequate support in their learning activities (Anders & Rossbach, 2015;Bruns, Eichen & Gasteiger, 2017;Nganga, 2020;).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review reveals that an excellent pedagogical knowledge has a significant correlation with effective teaching and learning in the classroom (Zamri & Fadhil, 2014;Jamil, 2012;Lo, 2014;Sulatan, Masnan, Rohaizad & Salleh, 2016). Teachers need the knowledge to develop the skills and to design quality learning activities that provide children adequate support in their learning activities (Anders & Rossbach, 2015;Bruns, Eichen & Gasteiger, 2017;Nganga, 2020;).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the research based curricula provided for preschool teachers is often not put into use. A study conducted in 2014 found that preschool teachers rarely use a math curriculum, and when they do, they pick and choose pieces of the full curriculum (Lo, 2014). The Kindergarten Common Core Standards for Mathematical Practices require that kindergartners fully understand cardinality, yet the time that is spent on math is often filled with reciting the count list and recognizing the Arabic numerals.…”
Section: Numeracy Research Often Absent From Preschool Educationmentioning
confidence: 99%
“…One of the most important goals for the Wesleyan Preschool-Math Project is that teachers will find it realistic and easy to implement in their classroom. Research focused on teachers' opinions about current curricula determined what teachers weren't getting from preschool math curricula (Lo, 2014). Lo reported that most teachers don't follow criteria in the instructed order or time frame, as these criteria are often unrealistic in a preschool setting.…”
Section: Teachers' Use Of Existing Curriculamentioning
confidence: 99%
See 2 more Smart Citations